Using telehealth clinical case vignettes to enhance clinical confidence and competence in veterinary students - Lubbers, Brian V.; Fajt, Virginia R.; Teller, Lori M.; Apley, Michael D.; Stillisano, Jacqueline (Frontiers in Veterinary Science, 2023)
Veterinarians contribute substantially to the health of their patients and enhance the communities in which they live. Delivery of veterinary curricula continue to evolve to ensure that veterinary graduates are prepared to meet their professional obligations on Day One of their careers. In this study, veterinary practitioners were recruited to deliver telehealth case rounds to veterinary students at Kansas State University and Texas A&M University. Case discussions were hosted virtually once per month in the 2020-2021 and 2021-2022 academic years for a total of 16 sessions. Each presenting practitioner was instructed to develop a brief presentation for a case routinely seen in their practice, and to discuss important clinical decision points in diagnosis, treatment and management. Cases could also highlight important ethical or communication issues encountered in veterinary medicine. The overall goal of this project was to increase the quantity and diversity of clinical cases to which veterinary students were exposed during their professional training. Student participants were surveyed to determine the effectiveness of telehealth sessions in increasing overall confidence and competence in case management, and veterinary presenters were surveyed to determine motivations for participating in the project and perceived value of the telehealth sessions.